Avaliação da atividade imunossupressora de moléculas isoladas de vegetais e derivados sintéticos in vitro e em modelo de endotoxemia - Costa, José Fernando Oliveira (2010)
The screening of bioactive molecules isolated from natural products have acquired a great importance due to the need of discovering new chemical entities for the development of safe and effective medicines, aiming at the treatment of several diseases, including the immunomediated ones. It is estimated that thousands of people around the world suffer with sepsis, one of the most important causes of death. In this work, were evaluated molecules isolated from vegetables and synthetic derivatives in in vitro assays of inhibition of NO production by macrophages and activated lymphocyte proliferation and in in vivo model of LPS-induced endotoxemia. Among the molecules tested, we selected 10 with in vitro (benzopyrone, hydroxicoumarin, solidagenone, lapachol and its syntethic derivatives α-lapachone, nor-lapachol, α-I-lapachone, β-I-lapachoneandacetylated isolapachol) or in vivo (benzopyrone, solidagenone, lapachol and derivatives nor-lapachol and β-I-lapachone and betulinic acid) activities. Benzopyrone and betulinic acid (BA) were the most active molecules in vivo, protecting mice challenged with a lethal dose of LPS and inhibiting TNF-α production. These effects were related to the overproduction of IL-10 and IL-10-/- mice were not protected when treated with BA in comparison to the IL-10+/+ treated with the drug, indicating the importance of this cytokine in the protection. Both molecules, benzopyrone and BA, inhibited the TNF-α production by macrophages when administered in vivo but not in vitro, suggesting their metabolism in vivo, generating active metabolites. In conclusion, we identified in vivo immunossupressor molecules, inhibiting the TNF-α production and with a potential use in the treatment of sepsis.